Designing the Future of Experiential Learning Environments for a Post-COVID World: A Preliminary Case Study - Markel, Julia M.; Guo, Philip J. (2020)
ABSTRACT Experiential learning environments such as computer labs and design studios are critical for learning hands-on skills like programming, design, and data science. However, during and even after a global pandemic many people will not be willing to congregate in such high-density physical spaces due to safety concerns. How can we design experiential learning environments of the future to make them broadly accessible regardless of whether students can be physically present? To spur discussion about this question, we performed a preliminary case study where we compared in-person and online versions of software-based design courses created before and during the early-2020 COVID pandemic, respectively. We found that online tools such as videoconferencing, chat, and screensharing worked better than their in-person counterparts for certain user needs, but they cannot foster as much ambient awareness or spontaneous interaction. We then offer design recommendations for how to improve remote learning tools to potentially match or exceed face-to-face interactions. We hope our work can inspire discussion at this symposium about how we can design better learning environments to prepare people for the new future of work in a post-COVID world. Keywords remote learning technologies, experiential learning ABOUT THE AUTHOR/S Julia M. Markel UC San Diego jmarkel@ucsd.edu Philip J. Guo UC San Diego pg@ucsd.edu Philip Guo is an associate professor of cognitive science at UC San Diego. His research spans human-computer interaction, programming tools, and online learning. He currently studies what motivates people to learn programming and builds tools to help people better understand code and data (e.g., http://pythontutor.com/). Academic website: https://pg.ucsd.edu/ New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).